THE STUDY OF THE SERBIAN LANGUAGE AND LITERATURE AT THE INSTITUTE FOR SERBIAN CULTURE PRIŠTINA – LEPOSAVIĆ (ON THE EXAMPLE OF COLLECTING AND EDITING WORK IN THE FIELD OF FOLK AND ARTISTIC LITERATURE (Heritage, 2026)
As part of a more extensive research project, the aim of which was to present the work of the Institute for Serbian Culture Priština – Leposavić by departments, i.e., fields and scientific disciplines, as well as a subproject dedicated to the study and preservation of the Serbian language and literature at the Institute, it has been planned to publish a series of papers which view this area primarily through publishing activities – dictionaries, collecting and editing work in the field of folk and artistic literature. Subsequent papers will illustrate the study of the aforementioned scientific discipline through monographic publications (historical-literary monographs, monographs dedicated to individual creative poetics, but also those which comprehensively address a single topic or subject, that is, a linguistic area, including books of essays and studies), through other forms of publishing (thematic collections of papers and proceedings of scientific conferences, bibliographical, and serial publications, i.e., the journal Baština), as well as through non-publishing activities (organisation of scientific conferences, round-table discussions, book promotions, collections of papers, journals, and the Institute itself), literary and institutional co-operation with scientific and cultural institutions, researchers’ guest appearances on thematic scientific radio and TV programmes, etc.Thus, this paper is the first in the series of contributions to the study of the Serbian language and literature through the publishing activities of the Institute for Serbian Culture. As a necessary cultural-historical and institutional context, the introductory part depicts the struggle to establish the Institute for the study of Serbian culture in Priština, outlining its scientific, cultural, and national objectives as well as presenting a concise history of its activities. Attention is then directed to the classification, number, and a concise review of publications dedicated to the study of the Serbian language and literature, while the central part of the paper is devoted to the analysis of collecting and editing work in the field of folk and artistic literature, with a special focus on the prefaces of collections of folk literature, anthologies, and chrestomathies, along with a book of edited critical texts with a significant introductory study (preface) and a bibliographical contribution. Owing to their scientific, cultural, and national value, particular attention was given to two scientific achievements – the project involving documentation and publication of Students’ Records of Serbian folk literature in the territory of Kosovo and Metohija, which was conducted under the guidance of Professor Vladimir Bovan and proved to be invaluable due to the exodus of Serbs in this territory, as well as the project involving collection and sistematisation of verbal folklore in the territory of Levač and Temnić conducted by Velibor Lazarević, a scientific associate of the Institute.Through a review and analysis of the aforementioned publications, the aim of the paper is to highlight the thematic, methodological, and socio-ideological frameworks within which the researchers and associates of the Institute approached Serbian folk literature and anthological work, to point out unexplored areas, and to emphasise the significance of the Institute’s publishing activities as one of the key forms of scientific engagement in the preservation and interpretation of Serbian literary and linguistic heritage.
Keywords: Institute for Serbian Culture Priština – Leposavić, publishing activities of the Institute for Serbian Culture, the study of language and literature, collecting and editing work, prefaces, folk literature, Students’ Records, Vladimir Bovan, anthologies, chrestomathies.